2013
DOI: 10.2196/jmir.2555
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Family Physician Trainees and Trainers Regarding the Usefulness of a Virtual Community of Practice

Abstract: BackgroundTraining for Australian general practice, or family medicine, can be isolating, with registrars (residents or trainees) moving between rural and urban environments, and between hospital and community clinic posts. Virtual communities of practice (VCoPs), groups of people sharing knowledge about their domain of practice online and face-to-face, may have a role in overcoming the isolation associated with general practice training.ObjectiveThis study explored whether Australian general practice registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…This is in keeping with the feedback from exploratory studies on intention to use [12,13] and in keeping with other studies on information technology usage [20]. Previous studies have described users overcoming barriers if perceived usefulness was high; a number of participants in this case study demonstrated this by using the site despite having concerns [11,20].…”
Section: Discussionsupporting
confidence: 84%
“…This is in keeping with the feedback from exploratory studies on intention to use [12,13] and in keeping with other studies on information technology usage [20]. Previous studies have described users overcoming barriers if perceived usefulness was high; a number of participants in this case study demonstrated this by using the site despite having concerns [11,20].…”
Section: Discussionsupporting
confidence: 84%
“…Adult learning theory was used as a vehicle for the idea of learner‐centredness . Experiential learning was used as a vehicle for learning in the context of doing, and communities of practice theory was used as a vehicle for the idea of people working together with a common purpose …”
Section: Resultsmentioning
confidence: 99%
“…47,48 Experiential learning was used as a vehicle for learning in the context of doing, 40,49 and communities of practice theory was used as a vehicle for the idea of people working together with a common purpose. [50][51][52][53] Theory providing a methodological tool Some authors gave theory the task of introducing or crafting methodological tools. These included tools for collecting data, tools for typology and tools for analysis.…”
Section: Theory As a Vehicle For An Ideamentioning
confidence: 99%
“…Examples of these include: educating and interacting with patients, reducing email communication, effective use of time, and collective learning. Some of these reasons were discussed as part of the main categories presented 18 above. Some others were mentioned less frequently or were perceived by the participants as useful but less important reasons to use social media.…”
Section: Brandingmentioning
confidence: 99%